2003
DOI: 10.1097/01.ta.0000051601.60556.fc
|View full text |Cite
|
Sign up to set email alerts
|

Time to Deterioration of the Elderly, Anticoagulated, Minor Head Injury Patient Who Presents without Evidence of Neurologic Abnormality

Abstract: Elderly, anticoagulated patients with minor head trauma risk neurologic deterioration within 6 hours of injury, despite an initially normal neurologic examination. Early cranial computed tomographic scanning and close observation for a minimum of 6 hours are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…Although the RR of ICH did not reach statistical significance in this subgroup from a clinical perspective, a subtherapeutic INR level would appear not to be protective of ICH in anticoagulated patients with blunt head trauma. This conclusion is consistent with the findings of Reynolds et al ,15 who reviewed a case series of 32 WHI patients over a 7-year period, where eight patients (25%) were found to have ICH, and two of these had a subtherapeutic INR (1.6 and 1.5). Our sample size is small and therefore statistically significant conclusions cannot be drawn.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the RR of ICH did not reach statistical significance in this subgroup from a clinical perspective, a subtherapeutic INR level would appear not to be protective of ICH in anticoagulated patients with blunt head trauma. This conclusion is consistent with the findings of Reynolds et al ,15 who reviewed a case series of 32 WHI patients over a 7-year period, where eight patients (25%) were found to have ICH, and two of these had a subtherapeutic INR (1.6 and 1.5). Our sample size is small and therefore statistically significant conclusions cannot be drawn.…”
Section: Discussionsupporting
confidence: 92%
“…Mina et al 7 found that the INR for their patients who died was 3.3±1.6 compared with 3.0±2.1 for the survivors. Reynolds et al 15 failed to observe a statistically significant difference in mean INR values between the group of patients without intracranial injury and those found to have ICH on the scan (p=0.59), although only eight out of 24 patients in the first group were tested. More importantly, they found no statistically significant difference between those with ICH who remained stable and those who subsequently deteriorated (p=0.12).…”
Section: Discussionmentioning
confidence: 94%
“…Although delayed appearance of intracranial hematomas most frequently occurs in the setting of severe TBI, they have been associated with coagulopathy. 21 Conversely, because the majority of patients in this study did not have a CT until clinical deterioration, they may have harbored an intracranial hemorrhage that "enlarged" secondary to underlying anticoagulation. It is well known that minor TBI patients have a clear risk of significant pathologic CT scan findings-up to 10% with GCS scores of 15; 20% with GCS scores of 14; and 35% with GCS scores of 13.…”
Section: Discussionmentioning
confidence: 94%
“…Two points in time, 12–24 h and 24–48 h after the admission CT scan, tended to show the radiographic maximal CT evolution for traumatic subarachnoid haemorrhage 27. Reynolds et al found that elderly patients with mild TBI taking anticoagulants who deteriorated after an initially normal neurological examination had a mean deterioration time of 6 h 39. Some previous investigators have claimed that final haematoma size is reached by 12 h in 84% of trauma patients,40 while others have reported that this occurs in only about 6–29%.…”
Section: Discussionmentioning
confidence: 99%